What is your organization's IQ?-A practical tool to gauge enterprise intelligence - (:unkn) unknown (My University, 2013)
Every day, organizations create thousands of invaluable information but many of them just fly away with leaving no mark behind. To avoid this undesirable loss, organizations build knowledge management (KM) systems to keep the information recorded in the organization's knowledge base. With increasing investments in KM implementations, measuring organizational benefits of KM initiatives has become an important agenda among KM practitioners. Measuring knowledge provides a mechanism to evaluate, control, and improve on existing performance and forms essential linkages between strategy and actions. The current study proposes that organizations have intelligence which is defined as ability to acquire and apply knowledge skills. They create information from data, identify new information adding value to its processes through analysing the information gathered and use the information in its processes. All these indicate a need for a scale to measure Enterprise Intelligence Index (EII) in order for better understanding of an organization's ability to keep and manage information. To develop EII, total 42 item scale was constructed. 144 mid or senior level IT, HR, CRM, sales, marketing managers of leading finance, IT, telecommunications, FMCG companies in Turkey responded to the survey. Due to the composite structure of the index, the factorial structure was analysed with explanatory and confirmatory methods. The results indicated that there were 8 broad factors of EII-Leadership and Vision, Organization and Structure, Culture, Partnerships, Processes, Measures, Competencies, Technology and Infrastructure with significant level of item loadings. These factors explained the total 53% of overall EII with acceptable levels of inter-item consistency. The study was one of the first steps in understanding the difference between what organizations is currently doing and what it needs to do in order to maintain and improve its performance level regarding with EII. At the macro level the index will enable organizations to compare themselves with each other. At the micro level, it calls attention to areas needing improvement in current and future initiatives. In either case, the index provides robust indicator and basis for decision making and organizational support and development. By the help of EII, organizations will be able to monitor their own progress among years as well as they can benchmark their status compared to the competition at any given time.
Keywords: Assessing knowledge management capabilities; Corporate knowledge management; Enterprise intelligence index